Assessment of Patient Safety Culture Amongst Pharmacy Staff of Selected Healthcare Facilities in Delta North, Nigeria - Arute, John Edjophe; Osarenmwinda, Monday Ikponmwosa, Omotejohwo Emily Okolosi-Patani (Sciences of Pharmacy, 2024)
The strategy for improving patient safety in hospitals heavily relies on safety culture. The study aimed to evaluate patient safety cultures amongst pharmacy staffs of selected health facilities in Delta North, Delya State, Nigeria. Data on patient safety amongst 70 pharmacy personnel in two major secondary and 5 general health facilities across Delta North senatorial district, Delta State, were collected using the Hospital Survey on Patient Safety Culture (HSOPSC) tool. Information on communication openness, the frequency of documenting different types of mistakes, as well as the overall patient safety culture rating, was collected. Composite scores were analyzed using SPSS version 22. Measurement data were presented as mean ± standard deviation (SD) and compared using a student t-test. The results were considered significant at p<0.05. The mean scores of all the various composite item responses were calculated and grouped into positive and negative responses with a mean score of ≥4 and <4, respectively. The safety cultures of physical space and environment, staff training and skills, and communication openness had a good composite score of 4.0 – 4.1. The safety culture of procedures for communicating prescriptions across shifts was poorly rated, with composite scores of 3.8. The safety culture of patient counselling had the highest composite score of 4.3. The safety composites for documenting various shades of mistakes had a mean score of 3.5. Overall, 68.1% of the healthcare facilities were rated excellent, although there were some loopholes (documenting mistakes and poor communication across shifts) in the safety composite scores requiring areas for improvement.